Human rights in the configuration of a plural governance (Revista cientifica In Vestigium Ire, 2019)
The intention of the writing itself is to observe the dependence established between the contemporary State as an administrative and political apparatus, and human rights; as well as to establish the acquired position of civil society-as a concept- in the face of governance processes and their materialization within public policies, all linked to the conceptual kaleidoscope represented by ideas on democracy and development; to this end, with respect to each of the tapies, the text will be divided, having as a guiding thread the structured political exercise based on human rights and its relationship with civil society.
Keywords: human rights; governance; public policy; development